THE SAMOTHRACE EARTHQUAKE OF MAY 2014 AND THE DISPLACEMENTS ESTIMATIONS USING PERMANENT GPS STATIONS DATA - Bitharis, S.; Fotiou, A.; Pikridas, C.; Rossikopoulos, D.; Pavlides, S.; Chatzipetros, A. (Bulletin of the Geological Society of Greece, 2016)
The contribution of GPS networks in monitoring seismic events is important because they can provide a direct geometrical information on the Earth's crust using satellite observations In this study position displacements of permanent GPS stations are determined due to intense seismic events in the North Aegean area after the strong earthquake on May 24, 2014. The horizontal coseismic displacements for the Samothrace Island were estimated at 9.4 cm and for Lemnos Island at 5.2 cm respectively. A study period of seven days was enough to show that the deformation evolved into two days.